The sensory and flavor characteristics of Shaoxing Huangjiu (Chinese rice wine) were significantly influenced by micro‐oxygen and electric field. Issue 11 (10th September 2021) - Shen, Chi; Zhu, Hongyi; Zhu, Wenxia; Zhu, Yimeng; Peng, Qi; Elsheery, Nabil I.; Fu, Jianwei; Xie, Guangfa; Zheng, Huajun; Han, Jiongping; Hu, Baowei; Sun, Jianqiu; et al.
Abstract: In order to improve the high cost of equipment and difficult management caused by the natural aging of Chinese rice wine (Huangjiu), micro‐oxygen (MO) and electric field (PEF) technology are used to accelerate the aging of Huangjiu. The results showed that micro‐oxygen and electric field have a significant effect on the sensory characteristics and flavor characteristics of Huangjiu. Compared with the naturally aged Huangjiu, the flavor compounds of Huangjiu treated with micro‐oxygen and electric field increase significantly. Based on principal component analysis, Huangjiu processed at 0.35 mg L/day or 0.5 mg L/day combined electric field exhibited similar flavor to the natural aged Huangjiu, which was highly associated with long‐chain fatty acid ethyl esters (C13–C18). Moreover, partial least squares regression demonstrated that sensory attributes of cereal aroma and astringency were highlighted after aging time, while fruit aroma, continuation, and full body were dominant after micro‐oxygen and electric field treatment. Micro‐oxygen and electric field effectively enhanced the quality of Huangjiu, which could be applied in other alcoholic beverages. Abstract : 1. Artificial aging technology affects the sensory and flavor changes of Huangjiu.2. Micro‐oxygen and electric field mixed treatment improve the quality of Huangjiu.3. Artificial aging technology effectively improves the sensory properties of Huangjiu.